Native and invasive ants affect floral visits of pollinating honey bees in pumpkin flowers (Cucurbita maxima) - Anjana Pisharody Unni (Nature Portfolio, 2021)
Abstract Global pollinator decline is a major concern. Several factors—climate change, land-use change, the reduction of flowers, pesticide use, and invasive species—have been suggested as the reasons. Despite being a potential reason, the effect of ants on flowers received less attention. The consequences of ants being attracted to nectar sources in plants vary depending upon factors like the nectar source's position, ants' identity, and other mutualists interacting with the plants. We studied the interaction between flower-visiting ants and pollinators in Cucurbita maxima and compared the competition exerted by native and invasive ants on its pollinators to examine the hypothesis that the invasive ants exacerbate more interference competition to pollinators than the native ants. We assessed the pollinator's choice, visitation rate, and time spent/visit on the flowers. Regardless of species and nativity, ants negatively influenced all the pollinator visitation traits, such as visitation rate and duration spent on flowers. The invasive ants exerted a higher interference competition on the pollinators than the native ants did. Despite performing pollination in flowers with generalist pollination syndrome, ants can threaten plant-pollinator mutualism in specialist plants like monoecious plants. A better understanding of factors influencing pollination will help in implementing better management practices.